Normal, inflammation and necrosis pulp radiograph image using 3D cone beam computed tomography - Pramanik, Farina; Firman, Ria Noerianingsih; Oscandar, Fahmi; Epsilawati, Lusi (Padjadjaran Journal of Dentistry, 2016)
Introduction: Abnormalities of the dental pulp can have several different diagnoses. Therefore, the dental pulp characteristics must be known in more detail and clear so that diagnosis be established more precisely and accurately.  One characteristic of the pulp can be seen from the density value through the 3D Cone Beam Computed Tomography (3D CBCT). Methods: The study  was  conducted  with  a  simple  descriptive  method.  The population is all the data 3D CBCT of patients who visited the Universitas Padjadjaran Dental Hospital (RSGM Unpad) in 2012. Samples of the research were 75 pulps  with normal, inflammation, and necrosis conditions and calculate the average density value. Results: Density values for dental pulps in the normal teeth between 465 - 775 HU, the inflammation teeth between 243.5 - 396 HU, and necrosis teeth between - 461.5 - -170 HU. Conclusion: There are differences in dental pulp density between the normal pulp, inflammation and necrosis through 3D CBCT.